Empirical study of the relationship between board of director mechanisms and perceived performance of listed firms in Nigeria - Hussani, Suleiman Muhammad (CSRC Publishing, 2017)
Purpose: The growing debate on the board of director mechanisms to firm performance will for a long time remain area of research. The effectiveness of the board of director composition, responsibility, and accountability have become an area of research in the recent trend. This paper attempts to investigate the empirical study of the relationship between the board of director mechanisms and perceived performance of listed firms in Nigeria. The underpinning theory of the paper is rooted in agency theory and supported by resource dependence theory, and stewardship theory to increase the understanding of the influence of the board of director formation to perceived firm performance. The questionnaires were administered to the respondents, out of 182 questionnaires administered, 117 were returned. The number of valid questionnaires is 114. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Empirical findings showed that board of director composition and accountability were positively associated with perceived firm performance. While the board of director responsibility has no relationship. Based on the knowledge of this paper, this is the first study that adopts the use of primary data to investigate the empirical study of the relationship between the board of director mechanisms and perceived performance of listed firms in Nigeria. The findings provide policymakers, stakeholders, and government with the approaches to overcome and resolved the conflict of interest between the board of director (agent) and shareholder (principal). The paper also offers some suggestions for future study.